Mekanisme Pengelolaan Persediaan Sparepart Sepeda Motor Honda Pada PT. Bintang Motor Jaya, Tbk Cabang Cirebon - Ariyani, Misriah (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2020)
Nowadays, the purchase of motor vehicles is rife among the People of Indonesia, especially Honda motorcycles. Increasing sales figures from year to year resulted in the maintained quality of the brand in all aspects both in terms of smh unit quality, service quality from smh official workshop, as well as the quality of genuine parts SMH or commonly known as honda genuine parts. The purpose of this research is to observe the mechanism of managing spare parts inventory at PT. Star Motor jaya Kab. Cirebon to improve the flow in and out of spare parts to be more organized and avoid the risk of undisciplined stock and so that the ordering process does not take long so that branding to consumers is maintained. At PT. Bintang Motor Jaya is in inputting its stock using stock cards as notes in and out of spare parts that are then inputted in the computer system. Although it already looks perfect in its flow, there are still irregularities in inventory that do not correspond that cause losses to the company whileordering the original parts often occura rather long delay that causes disappointment to customers so it is important to make improvements in the infrastructure of its management mechanism bothin terms of human resources and control of the process. This research was conducted by descriptive method, where data collection techniques are carried out with observations, interviews, field studies, and literature. This research was conducted as a problem solving of the lack of regular inventory management and quality improvement in terms of ordering time and anticipation of handling if there are still errors in that aspect.